Membangun UMKM Pangan Halal Menuju Desa Berdaya dan Berdaya Saing - Amelia HK, Lenny; Agusseptiany, Tamma Zahra (Ma'soem University, 2025)
Cilame Village in Kutawaringin Subdistrict, Soreang, has significant potential for local food production, particularly for micro, small, and medium enterprises (MSMEs). However, many entrepreneurs in this village still lack understanding of the importance of halal food certification as a tool to enhance consumer trust. Without halal certification, their products are often perceived as less credible, especially in today's modern era where consumers are increasingly aware of food quality and safety. Furthermore, limited market access remains a major challenge for local producers. Therefore, socialization of halal food certification is urgently needed to assist MSMEs in improving their product competitiveness and maintaining consumer confidence. The method employed in this mentoring and socialization activity is the Community-Based Participatory Research (CBPR) approach, which was chosen to ensure the active involvement of local food Micro, Small, and Medium Enterprises (MSMEs) in Cilame Village. The results of the activity show that the socialization of halal certification in Cilame Village successfully increased the commitment of MSMEs to halal certification, with knowledge increasing by up to 47% and 80% of MSMEs ready to register. Sustained success requires further technical interventions, namely NIB/SIHALAL desk clinics and practical halal GMP education. This activity builds a strong foundation for a competitive village through halal product assurance and certification.